Predictors of Institutional Delivery in Nigeria: A Multilevel Mixed-effect Analysis of the Nigeria 2013 DHS - KUPOLUYI, Joseph Ayodeji; MUMMA, Jane (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Deaths of women during pregnancy and childbirth still remain a major reproductivehealth risk in Nigeria with institutional delivery of 37%.Objective: The study assessed the effects of individual and community-level factors on the use ofinstitutional delivery in Nigeria.Methods: A multilevel logistic modeling was employed on data from the 2013 NigeriaDemographic and Health survey with a sample of 20,467 women aged 15–49 years who had a livebirth during the 5 years preceding the survey.Findings: The result shows that delivery in a health facility was high in communities with highestmaternal education (OR=11.43, p<0.01), highest wealth (OR=5.9, p<0.01), high level of ANCutilization (OR=1.8, P<0.05) and low in communities where distance to health facilities was a bigproblem (OR=0.5, p<0.05). The ICC (30.1%) and PCV (76.1%) indicate that both community andindividual level factors explained the variations in institution delivery.Conclusion: The study suggests that poverty level; ANC visits, distance to health facility andeducation should be addressed to increase the number of deliveries in health facilities.